WATERMELON INITIAL GROWTH UNDER DIFFERENT HYDROGEL CONCENTRATIONS AND SHADING CONDITIONS - Pereira, Breno de Jesus [UNESP]; Rodrigues, Gustavo Araujo; Santos, Anacleto Ranulfo dos; Anjos, Gilvanda Leao dos; Costa, Franciele Medeiros (Univ Fed Rural Semi-arido-ufersa, 2019)
Watermelon (Citrullus lanatus) belongs to the plant family Cucurbitaceae. It is cultivated in many regions of Brazil, particularly in rainfed areas; thus, it is subject to the problems arising from irregular rainfall. Hydrogel is a soil conditioner used to retain and provide water to plants for long periods of time. Therefore, incorporating hydrogel into the soil should increase water availability for watermelon cultivation, and may be an alternative method to reduce the risk of water deficit. This study evaluated the effect of different concentrations of hydrogel on the initial growth of watermelon cv. 'Crimson Sweet' under different shading conditions. The experiment was carried out in a greenhouse with completely randomized design with a 4x3 factorial scheme. The treatments consisted of four hydrogel doses (0.0; 1.5; 3.0; and 6.0 g L-1 substrate), three shading conditions (under full sun; black shade net, and red shade net, both with 50% shading), and five replicates per treatment. The variables evaluated were plant height; stem diameter; shoot, root, and total dry matter; and leaf area. The best hydrogel dose for watermelon cultivation was 1.5 g L-1, but the higher doses impaired plant growth, regardless of shading conditions. The black net improved biomass accumulation in 'Crimson Sweet' watermelon, whereas the red net induced plant etiolation.
Keywords: Citrullus lanatus; Soil conditioner; Shade nets